Implementasi Metode Weighted Produk (WP) Sistem Penunjang Keputusan Dalam Menentukan Prestasi Guru - Saprudin; Rengga Herdiansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The history of the concept of a decision support system was first introduced in the early 1970s by Michael S. Scott Morton with the term Management Decision System (Tampubolon, 2010). The system is a computer-based system that aims to assist decision making by utilizing existing data and models. The main task of the teacher is to educate, teach, guide; direct, train, assess; and assess students. Outstanding teachers are teachers who have the ability to carry out tasks, are successful in carrying out tasks, have a personality that is in accordance with the teaching profession and have educational insights. A decision support system or Decision Support System (DSS) is a system that can assist in making decisions in an organization or company by applying a method that is appropriate to the field of decision taken; Making decisions manually without the help of SPK will result in an assessment that is not or less objective. The process of selecting outstanding teachers at the school level has so far been carried out conventionally, namely based on the personal observations of the teacher concerned, and only based on certain criteria. So that in this way, not all criteria and sub criteria can be accommodated in the assessment. Therefore, it is necessary to apply information technology in the form of a Decision Support System, especially in the process of selecting issuing teachers so that the process becomes effective so that the criteria and sub-criteria can be accommodated in the assessment. One method of decision support that is quite popular and reliable in overcoming the problem of selecting objects according to the criteria measured qualitatively and quantitatively is the weighted product (WP) method. The weighted product (WP) method is one of the methods commonly used in election systems, the advantage of this method is the concept of improving the weights used for each criterion. Based on the problems and problem-solving plans above, in this writing the author takes the title "Method of Implementation of the Weighted Product (WP) Method of Decision Support Systems in Determining Teacher Achievement".